Rooting, Growth, and Maturation of Grape Cuttings Under Different Growth Regulators - Grigoryan, Bella; Grigoryan, Aelita; Ohanyan, Artem (ՀԱԱՀ հիմնադրամ)
With the development of viticulture in recent years, vineyard areas have increased and the demand for orchards with local varieties has grown. Propagation by cuttings is the most common method of grape propagation. The influence of growth regulators (zircon, heteroauxin, and kornevin) on the rooting, growth, and ripening of hardwood cuttings of grape varieties Voskehat, Garan Dmak, and Tozot was studied. The study shows that the use of growth regulators positively affects the growth and development of cuttings, strengthens roots, increases rooting, and promotes the growth and development of surface organs Among the regulators used, the best results were shown by growth stimulants heteroauxin and zircon. These stimulants can be used to ensure the high survival rates of less common varieties.
Keywords: Agronomy and Agroecology